An asymptomatic 16-year-old girl with anomalous left coronary artery from pulmonary artery (Bland-Withe-Garland syndrome) - Polak, Gwidon; Białoszyński, Tomasz; Motyl, Dorota; Hoffmann, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
A 16-year-old girl was referred to our hospital to perform cardiac multi-slice computed tomography (MSCT) due to an unclear view of coronary arteries in echocardiography performed during a routine visit to the cardiology clinic. As an infant she was hospitalized due to signs of severe heart failure, and while in hospital she underwent cardiac arrest. However, ever since this incident she has not experienced any cardiovascular symptoms, and still remains asymptomatic. On physical examination we found systolic murmur localized to the left sternal border. In echocardiography the dimensions of cardiac chambers and ventricular contractility were normal. Cardiac MSCT demonstrated markedly dilated tortuous right coronary artery (RCA), giving very well-developed collaterals crossing the interventricular septum toward the left coronary artery (LCA). The LCA was also dilated but not as much as the RCA. The images showed an anomalous origin of the LCA from the pulmonary artery trunk (ALCAPA) and suggested retrograde filling of the LCA through collaterals from the RCA and emptying into the pulmonary artery trunk (PA). Coronary angiography and aortography confirmed the diagnosis of ALCAPA (Bland-White-Garland syndrome). It showed a very big tortuous RCA, the LCA filling retrogradely through collaterals from the RCA and draining into the PA. Anomalous left coronary artery from pulmonary artery is a congenital anomaly associated with early infant mortality, very rarely diagnosed in asymptomatic adults, with uncertain but probably poor prognosis. MSCT is useful for diagnosis. The patient still remains asymptomatic and so far she and her parents have not agreed to surgical treatment.